Aggregation enhanced photoactivity of photosensitizer conjugated metal nanoparticles for multimodal imaging and synergistic phototherapy below skin tolerance threshold. (August 2022) - Tian, Sichao; He, Jiangling; Lyu, Da; Li, Shuang; Xu, Qing-Hua
Abstract: Phototherapy techniques such as photodynamic therapy (PDT) and photothermal therapy (PTT) have aroused extensive interest as powerful cancer therapy techniques because of their advantages of minimal invasiveness. However, conventional PDT/PTT agents usually suffer from low efficiency and drawback of no imaging capability. Metal nanoparticle conjugates have been recently demonstrated to display a new type of aggregation induced emission, making them attractive multifunctional therapeutic agents. Herein, we designed Chlorin e6 (Ce6) conjugated gold nanoparticles (Au NPs) that displayed significantly enhanced one- and two-photon excitation fluorescence, singlet oxygen ( 1 O2 ) generation and photothermal effects. The photoactivity of Ce6-Au NPs was suppressed in the isolated form and became significantly enhanced in the aggregated form, together with significantly improved photostability owing to shortened emission lifetime. By forming aggregate in-situ inside cancer cells, aggregated Ce6-Au NPs were utilized to act as the fluorescence imaging probes under one- and two-photon excitation using red and near-infrared light, respectively. The aggregated Ce6-Au NPs also displayed excellent PDT and PTT performance and can effectively eradicate cancer cells by using red light continuous wave lasers with power density below the skin tolerance threshold. This plasmonic nano-system offers a promising potential for imaging guided PDT/PTT synergetic therapy, which might open a new venue to explore safe, and noninvasive theranostics. Graphical Abstract: ga1 Highlights: Aggregated Ce6-Au NPs display enhanced 1PE and 2PE fluorescence, 1 O2 generation and photothermal effects. Both brightness and photostability of aggregated Ce6-Au NPs are significantly improved compared to free Ce6. Ce6-Au NPs can act as fluorescence imaging probe and synergistic phototherapy agent upon forming aggregates in-situ. Aggregated Ce6-Au NPs can effectively eradicate cancer cells by using red light with power below skin tolerance threshold.